2022
DOI: 10.1371/journal.pone.0278182
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent resilience and mobile phone addiction in Henan Province of China: Impacts of chain mediating, coping style

Abstract: Background As mobile phone use grows, so it brings benefits and risks. As an important part of adolescents healthy growth, resilience plays an indispensable role. Thus, it is important to identify when mobile phone use of an adolescent becomes an addiction. This study proposed to explore the effects of adolescent resilience on mobile phone addiction, and tested the mediating role of coping style and depression, anxiety, and stress (DASS) on phone addiction among 2,268 adolescents in the Henan province, China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Studies have suggested that compulsive Internet use can lead to difficulties in emotion regulation and low levels of emotion regulation can predict problematic internet use [ 6 , 7 ]. Among college students, mobile phone addiction is negatively associated with psychological resilience [ 8 ]. Problematic phone use is also moderately associated with depression and mild-to-moderately associated with anxiety [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that compulsive Internet use can lead to difficulties in emotion regulation and low levels of emotion regulation can predict problematic internet use [ 6 , 7 ]. Among college students, mobile phone addiction is negatively associated with psychological resilience [ 8 ]. Problematic phone use is also moderately associated with depression and mild-to-moderately associated with anxiety [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, neurotic personality has been reported to be positively associated with a tendency toward mobile phone addiction [12]. Moreover, loneliness has been linked to higher mobile phone usage frequency [13]; while negative coping styles were positively correlated with mobile phone addiction scores [14]. In their exploration of risk factors, researchers have put forward several theoretical models.…”
Section: Introductionmentioning
confidence: 99%